2008
DOI: 10.1021/la801416a
|View full text |Cite
|
Sign up to set email alerts
|

Micellization and Adsorption of a Series of Succinimide Dispersants

Abstract: The efficiency of a series of nonionic dispersants at stabilizing carbon-rich particles in oil was evaluated. The dispersants were synthesized by coupling a polyamine to two polyisobutylenes terminated at one end with a succinic anhydride (PIBSA). Their chemical composition was characterized by FTIR absorption. The associative strength of the dispersants was determined from their ability to self-associate in solution into reverse micelles. Their critical micelle concentration (CMC) and aggregation number (Nagg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 36 publications
0
51
0
Order By: Relevance
“…Therefore the increase in surfactant concentration led to the increase of reverse micelles in the continuous phase. However, it is worth mentioning that PIBSA-based reverse micelles in the oily phase of explosive emulsions contain ammonium nitrate in their core (Reynolds et al, 2000(Reynolds et al, , 2001 and that the associative strength (aptitude to induce self-assembly of surfactant molecules) originates from hydrogen-bonding between the surfactant head group and the ammonium nitrate solution (Ganguly et al, 1992;Shen and Duhamel, 2008). In previous studies utilising other succinimide dispersants, it was observed that PIBSA-based surfactants aggregate at low concentration (Viper et al, 1968;Shen and Duhamel, 2008).…”
Section: Dependence Of Elastic Properties On Droplet Size (Ds)mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore the increase in surfactant concentration led to the increase of reverse micelles in the continuous phase. However, it is worth mentioning that PIBSA-based reverse micelles in the oily phase of explosive emulsions contain ammonium nitrate in their core (Reynolds et al, 2000(Reynolds et al, , 2001 and that the associative strength (aptitude to induce self-assembly of surfactant molecules) originates from hydrogen-bonding between the surfactant head group and the ammonium nitrate solution (Ganguly et al, 1992;Shen and Duhamel, 2008). In previous studies utilising other succinimide dispersants, it was observed that PIBSA-based surfactants aggregate at low concentration (Viper et al, 1968;Shen and Duhamel, 2008).…”
Section: Dependence Of Elastic Properties On Droplet Size (Ds)mentioning
confidence: 99%
“…Thus, the effect of surfactant concentration can be understood from the fact that lower CMC is a reflection of both a high associative strength and a strong anchor of the polar head group onto the interface (Shen and Duhamel, 2008), and the effect of surfactant type from the ammonium nitrated-surfactant interaction.…”
Section: Dependence Of Elastic Properties On Droplet Size (Ds)mentioning
confidence: 99%
“…The effect of secondary amines on micelles formation was observed earlier for other succinimide surfactants. [8] …”
Section: Interfacial and Bulk Propertiesmentioning
confidence: 99%
“…[6,7] The bulk properties of succinic surfactants were investigated. [8] One of the most promising ways to examine the interface structure and interfacial interactions is to perform the IR spectroscopic study, particularly by using the FTIR analysis method. The IR-spectroscopy has been widely used to study the interactions between ions in solution, [9] polymer and surfactant interactions, [10] and interactions between electrolyte and surfactant in emulsions.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their immense importance to lubricating automotive oils, the structure, mode of dispersion, dispersion efficacy, and self‐assembly (i.e., reverse micellization) of PIB‐based dispersants in nonpolar media has been extensively studied, with the primary focus directed to PIBSI‐type dispersants . For example, using a ruthenium‐based probe and steady‐state fluorescence, Duhamel and Shen demonstrated that PIBSI dispersants self‐associate into reverse micelles within a nonpolar solvent, with the polyamine moieties shielded by a corona of PIB tails.…”
Section: Introductionmentioning
confidence: 99%